Quality Management and Academic Needs in UNMSM Qualified Athletes 2017 - 2019 - Díaz Rodríguez, Manuel Alexander (2020)
The developed article focuses on the ability to recognize and analyze the problems found in Sports Administration Management, specifically in the management for the academic support of the qualified student-athlete. It was possible to verify the high rate with student desertion in the athletes of UNMSM during the years 2017 – 2019. A descriptive study is also carried out through the collection of historical information, analysis of indicators in reports and official documentation of the planning department of UNMSM. In this research, it is demonstrated that there is a total lack of knowledge about the management of academic support for the qualified athlete. Through the adequate management of the Malcolm Baldrige model of quality, one can cover the student’s requirements using appropriate indicators, and can achieve continuous improvement by meeting the academic needs of qualified student-athletes.